NUMERICAL AND EXPERIMENTAL STUDY OF ULTRA LOW HEAD AXIAL WATER TURBINE - Raditya
Indonesia has a river with huge water potential to be used as a hydroelectric power plant. Based on Ministry of Energy and Mineral Resources data, from a number of river owned by Indonesia, the potential of water energy throughout Indonesia which has been utilized is under 10%. From these data, it appears that the utilization of water energy potential in Indonesia is still low. Average flowrate and head of rivers in Indonesia are not too high. The potential energy of water can utilized by ultra low head axial turbines as the driving force. PPEBT ITB was planning to construct those ultra low head turbin with designed blade to run at water condition of 128 kg/s massflow rate with 90 rpm angular velocity. Before the turbine was made, a simulation for turbine was conducted in ortder to predict the performace of the turbine. Experiment of the turbin was conducted by using direct shaft torque and angular velocity measurement. The simulation result shows the maximum efficiency of the turbine is 82,45 % at 95 rpm angular velocity and 135 kg/s massflow with 0,25 m head. Meanwhile, the experiment result shows that the turbine maximum efficiency is 79,21 % at 118 rpm angular velocity and same massflow.